Could natural killer cells compensate for impaired CD4+ T-cell responses to CMV in HIV patients responding to antiretroviral therapy? - Tan, D.; Fernandez, S.; French, M.; Price, Patricia (Academic Press, 2009)
We evaluated NK cell subsets and functions in previously immunodeficient HIV patients responding to ART. Cytokine receptor mRNA was quantitated in purified CD56+ cells. Data were correlated with CD4+ T-cell counts and IFN? responses to CMV. NK cell IFN? responses to K562 cells and proportions of CD56lo NK cells were correlated in patients (p < 0.001) and both were lower than in controls (p < 0.001 and p = 0.008, respectively), so all patients had poor NK cell function. Proportions of CD56hi NK cells correlated inversely with current CD4+ T-cell counts (p = 0.006) and perforin expression in CD56hi NK cells was higher in patients than controls (p < 0.05). Hence increased proportions and cytolytic function of CD56hi NK cells may partially compensate for CD4+ T-cell deficiency. NK cell IFN? responses correlated inversely with expression of IL-10 and IL-12 receptor mRNA. Expression of these transcripts is reduced by exposure to the cytokines, which may reflect immune activation in immunodeficient patients. © 2009 Elsevier Inc. All rights reserved.